It's a diagnosis for the rich: disability, advocacy and the micro-practices of social reproduction. Issue 2 (17th February 2023) - Nevill, Thomas; Savage, Glenn C.; Forsey, Martin
Abstract: A considerable body of sociological literature has examined the role that education plays in the ongoing reproduction of class-based inequalities. However, there is a relative lack of research that has focused on the reproduction of inequalities linked to the combined influences of disability and social class. Based on a qualitative study of 19 Australian families, this article examines how the strategies that mothers adopt to advocate for their dyslexic children are shaped by social class. We argue that the expectation by schools that mothers will advocate for their child reproduces inequality because advocacy hinges on mothers having access to specialised cultural capital and considerable financial capital. Our findings also indicate that there is a reliance on mothers to advocate for their child in order to get support. We argue that this reliance on advocacy shifts responsibility for inclusion from the state to mothers, further reproducing a system that is exclusionary of students with disabilities.